Case report: 17α− hydroxylase deficiency due to a hotspot variant and a novel compound heterozygous variant in the CYP17A1 gene of five Chinese patients - Li, Jinying; Zhang, Qiang; Chen, Jing; Fu, Xingjiao; Yang, Jingpin; Liu, Lijun (Frontiers in Pediatrics, 2022)
17a-Hydroxylase deficiency (17OHD) is a rare form of congenital adrenal hyperplasia (CAH).This disease is caused by mutations in the CYP17A1 gene, that impairs adrenal and gonads steroid biosynthesis, the patient presents with hypertension and hypokalemia, and disorder of sex development.Here, we describe five patients from three families with this rare disease of genotypes and phenotypes. May be for the founder effect, most of them with a hot spot Variant of c.985_987delTACinsAA in CYP17A1 gene, but the patients we found were younger and there is a pair of twins with the karyotype of 46, XX, and 46, XY, respectively, but they all have a female phenotype.Meanwhile, we identify A novel compound Heterozygous of c.1243+6T>G (p.Y329fs/splicing) in CYP17A1 gene.